2022
DOI: 10.1111/jgs.17997
|View full text |Cite
|
Sign up to set email alerts
|

You can't be what you can't see: A systematic website review of Geriatrics Online‐Visibility at US medical schools

Abstract: Background Graduating US medical students must build strong skills in caring for older adults, necessitated by shifting population demographics. Little is known, however, about current medical student exposure to geriatrics on a national scale. This systematic website review characterizes geriatrics opportunities at US medical schools, seen through the lens of publicly available information online. Methods Reviewers searched for 18 online Geriatrics Elements, in the domains of Information Prevalence, Geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Many may have never considered pain medicine, anesthesiology, or vascular surgery and so it would not cross their minds to carve out elective time for some specialties. For example, low visibility of geriatrics in the curriculum has been associated with low interest as a specialty [ 20 ]. Mandatory participation in a broad range of elective experiences interspersed throughout the third year would accomplish this with the added benefit of building knowledge and understanding for colleagues in other fields of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Many may have never considered pain medicine, anesthesiology, or vascular surgery and so it would not cross their minds to carve out elective time for some specialties. For example, low visibility of geriatrics in the curriculum has been associated with low interest as a specialty [ 20 ]. Mandatory participation in a broad range of elective experiences interspersed throughout the third year would accomplish this with the added benefit of building knowledge and understanding for colleagues in other fields of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study of 191 allopathic and osteopathic medical schools, only 45% had required a geritatic rotation for all students. 2 In 2017, the John A. Hartford Foundation and the Institute for Healthcare Improvement (IHI), in partnership with the American Hospital Association and the Catholic Health Association of the United States developed the "Age-Friendly Health Systems" with the dissemination of evidence-based care, known as the 4Ms. The 4Ms (What Matters Most, Mobility, Mentation and Medication) include a framework for history taking of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Given this dramatic increase, medical students' education compels training in communicating with older adults. However, in a study of 191 allopathic and osteopathic medical schools, only 45% had required a geritatic rotation for all students 2 …”
Section: Introductionmentioning
confidence: 99%
“…One such challenge is a lack of attention to the topic of geriatric medicine in the undergraduate curriculum in most medical schools in the United States. A recent systematic review of the websites of 191 MD-granting and DO-granting schools in the United States 18 found that only 45% of these schools included clinical activities related to geriatric medicine as part of their required curricula. The amount of attention in graduate medical education given to the care of older individuals depends certainly on the particular medical specialty, but the topic has been identified as a gap for resident and fellow training 19,20 .…”
mentioning
confidence: 99%